2016
DOI: 10.1111/nyas.13172
|View full text |Cite
|
Sign up to set email alerts
|

Resting in darkness improves downbeat nystagmus: evidence from an observational study

Abstract: Resting in an upright position during daytime decreases downbeat nystagmus (DBN). When measured in brightness only, that is, without intermitting exposure to darkness, it does not make a significant difference whether patients have previously rested in brightness or in darkness. In real-world scenarios, people are often exposed to brightness and darkness intermittently. The aim of this study was to analyze whether resting in brightness or resting in darkness was associated with a lower post-resting DBN after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Resting in upright position is thought to enable otolithic input to stabilize the already disinhibited SVN, causing upward drifting [18]. The same research group also showed resting in the dark decreased SPV by nearly two times the reduction when resting in bright conditions [119]. DBN also improves throughout the day and is at its worse in the morning when arising from sleep, usually in a supine position [7].…”
Section: General Treatment Of Downbeat Nystagmusmentioning
confidence: 92%
“…Resting in upright position is thought to enable otolithic input to stabilize the already disinhibited SVN, causing upward drifting [18]. The same research group also showed resting in the dark decreased SPV by nearly two times the reduction when resting in bright conditions [119]. DBN also improves throughout the day and is at its worse in the morning when arising from sleep, usually in a supine position [7].…”
Section: General Treatment Of Downbeat Nystagmusmentioning
confidence: 92%
“…Other influences can be considered, such as the role of extraocular proprioception (102), efference copy (103,104), sleep inertia, which is a transient state of reduced arousal that occurs immediately after awakening from sleep (105-107) and has a negative influence on Purkinje cell function. Finally, the effect of resting for 2 h in darkness was also considered, which significantly lowered the post-rest DBN, in contrast to the effect of resting in light (108).…”
Section: Circadian Modulation Of Dbnmentioning
confidence: 99%
“…A broad range of drugs has been investigated regarding their effect on different forms of nystagmus [69 & ]. For channelopathies as familial hemiplegic migraine, acetazolamide is effective for treating ] and resting in darkness for 2 h (compared with remaining in bright light), resulting in a relative reduction of vertical slow-phase eye velocity by about one-third [73]. Advanced therapeutic interventions in acquired nystagmus include the attachment of a T-plate to the lateral orbital rim and the inferior rectus muscle tendon [74], the implantation of an oculomotor prosthesis [75] and retrobulbar botulinum-toxin A injections [76], resulting in reduced nystagmus amplitude and oscillopsia in all cases.…”
Section: Treatment Approaches To Nystagmus and Oscillopsiamentioning
confidence: 99%